2011
DOI: 10.4102/ajlm.v1i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mentorship on WHO-AFRO Strengthening Laboratory Quality Improvement Process Towards Accreditation (SLIPTA)

Abstract: BackgroundThe improvment of the quality of testing services in public laboratories is a high priority in many countries. Consequently, initiatives to train laboratory staff on quality management are being implemented, for example, the World Health Organization Regional Headquarters for Africa (WHO-AFRO) Strengthening Laboratory Management Towards Accreditation (SLMTA). Mentorship may be an effective way to augment these efforts.MethodsMentorship was implemented at four hospital laboratories in Lesotho, three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 5 publications
1
48
0
2
Order By: Relevance
“…This facility-based and embedded approach to mentorship has been observed to have high impact in different settings. 4,5 …”
Section: Facility-based Laboratory Mentorshipmentioning
confidence: 99%
See 2 more Smart Citations
“…This facility-based and embedded approach to mentorship has been observed to have high impact in different settings. 4,5 …”
Section: Facility-based Laboratory Mentorshipmentioning
confidence: 99%
“…3 A culture of practicing quality routinely is a behaviour change issue and calls for a different approach to training. 4 The Foundation of Health survey indicated that approaches that utilise active learning strategies, where participants put quality improvement into practice through close coaching and mentoring, are thought to be more effective than didactic classroom styles alone. 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 At the time that SLMTA was adopted, the country had already begun a structured mentorship programme with an embedded mentor. This mentor soon became certified as a SLMTA trainer so that he could enhance on-going mentoring efforts with the SLMTA programme.…”
Section: Lesothomentioning
confidence: 99%
“…32,35 This model has welldefined goals for each mentoring engagement, extended contact time on site, defined periods when mentors are absent, consistent approaches across laboratories and measurement of progress using standardised tools. Mentors may come from the laboratories they are assigned to mentor, from a local partner, or from outside the country.…”
Section: Human Resourcesmentioning
confidence: 99%